Promise and Pitfalls of Polytheism: A critique of The World Development Report 2017 - Shalini Randeria; Lys Kulamadayil (Revue Internationale de Politique de Développement)
This article offers a critical analysis of the 2017 World Development Report on Governance and the Law. The Report marks a shift away from the single-minded worship of the market (World Development Reports [WDR] 2000/2001 and 2002) as well as the elevation of the state and the rule of law to the World Bank’s pantheon (WDR, 2005). Its expansive polytheism now includes law and recognises its local plurality along with its imbrication in power asymmetries. This move to a capacious and diverse pantheon, which accommodates variety albeit at the expense of stringency, may possibly please those calling for a sensitivity to context instead of one-size-fits-all prescriptions. But it is unlikely to generate either a coherent theoretical perspective on law or a coherent set of policy recommendations. In terms of argument, language, and style, the Report is thus characterised by a curious disjunction between some important insights on the role of law in society on the one hand, and proposals on development governance on the other. The Report’s recognition of the double-edged nature of law and its acknowledgement of the vexed relationship between law, politics and power are weakened, for instance, by an exclusively positive appreciation of law’s functions in the policy arena. In view of its many unresolved tensions sustained in an attempt to cater to the tastes of a variety of different constituencies, the Report is likely to be less influential for development policy and practice than anticipated.